Blindness, rehabilitation and identity: a critical investigation of discourses of rehabilitation in South African non-profit organisations for visually impaired persons - Botha, Michelle (Division of Disability Studies, 2021)
This study explores the role of rehabilitation in shaping the subjectivity of blind persons. It considers what engaging with rehabilitation services might communicate to people with visual impairments about their status, their value and their place in the world. Rather than being concerned with the practical aspects of rehabilitation, it explores how rehabilitative practices operate at the symbolic level, and interrogates the meanings about blindness which are produced within relationships where help is given and received. Drawing on Foucauldian concepts, this research traces the interplay between discourse, power and knowledge in rehabilitation services. The research design includes two phases. Through analysing the website copy of eight organisations located across South Africa, Phase One identified discourses employed by organisations as they represent themselves in the public realm. In Phase Two, semi-structured interviews were conducted with eight service providers and eighteen service users across four organisations operating in the Western Cape province of South Africa. This phase identified the discourses framing rehabilitative activities and relationships. Visually impaired participants described sight loss as a significant trauma – as dislocation from society and self – revealing that service users might be particularly vulnerable to the shaping influence of rehabilitation. Data analysis found, firstly, that the discourses which frame rehabilitation services position visually impaired service users as passive recipients in relation to the work of service providers and the gifts of the public. This positioning objectifies service users and may signal to them that they are neither valued as stakeholders nor recognised as autonomous adults, while also requiring that they demonstrate gratitude towards service providers and the public. Secondly, rehabilitation is constructed as a linear journey with strictly defined outcomes. This ‘journey discourse' relies on polarised fantasies about blindness involving, on the one hand, dependency, dislocation and struggle and, on the other, independence, integration and coping. Visually impaired service users are required to demonstrate evidence of the latter while the former shadowy figure of pre-intervention blindness must be defended against. This discourse prohibits nuance and expressions of ongoing struggle, underpinning an imperative to cope found within organisations. Amid limiting discursive practices in rehabilitation, a key finding is that visually impaired service users are involved in complex negotiations of self and place. Investigating the discourses which frame and support rehabilitative practices sheds light on investments in promoting particular ways of being for visually impaired people, prompting us to consider what service providers, service users and, indeed, society as a whole might be colluding with. This work offers a novel perspective on blindness rehabilitation in South Africa as it explores an interplay between essential practical interventions found in rehabilitation and the influences on identity which those who experience sight loss undergo as they move into a new life with visual impairment.